The impact of Nigeria's corporate affairs commission reform and re-organization on corporate governance and service delivery - Yuguda, Madu Abdulrazak; Saidu, Idris (2014)
The pre-reforms period of the Nigeria’s Corporate Affairs Commission (CAC) was characterized by lack of standing system of tracking of companies’ compliance and general gross inefficiency in the delivery of services by the Commission.In 2001 CAC experienced reform and re-organization processes; meant to make it more responsive to discharging its regulatory role and achieving good corporate governance practices and efficiency in service delivery.The question is, has these processes strengthened the quality of services delivered by the Commission? The objectives of this paper are to highlight the components of the re-organization exercise of CAC and see how the reform has impacted on the Commissions’ performance.To achieve these, the paper employs the use of both empirical and secondary sources of data for analysis.The Service Quality Model was used as theoretical guide to the study.It was observed that the Commissions’ reform and re-organization has impacted in computerization of company registration process, improved human resource quality and even the introduction of new services. The paper, therefore, recommends that for good corporate governance practices to be achieved in Nigeria, the CAC should continue to strengthen its compliance and enforcement processes and procedures and also ensures that all the registered companies are continually monitored and sanctions enforced on defaulters.When compliance and enforcement mechanisms are reinforced, the Nigeria’s CAC would raise the confidence of investors and general public.